Uncovering psychologically mediated pathways to cardiovascular diseases: depressive symptoms as a mediator between childhood maltreatment and single or multiple cardiovascular disease comorbidities - Yu, Peilin; Zhang, Hong; Zhang, Xinxin; Zeng, Ping; Zheng, Chu; Wang, Ke (Frontiers in Psychiatry, 2025)
ObjectiveChildhood maltreatment (CM) increases the risk of cardiovascular disease (CVD), but the mediating mechanism of depressive symptoms in this process has not been fully elucidated. To further elucidate the potential mechanisms of depression in the association between CM and CVD, this study aimed to investigate the mediating role of depressive symptoms in a UK biobank cohort.MethodsCorrelation scales for CM types and depressive symptoms were first collected. Additionally, the diagnostic types of CVD were identified. Meanwhile, after controlling for child socioeconomic and demographic factors measured at baseline, we developed logistic regression models to analyze correlations and marginal effects among the three. Next, we used mediated causality modeling in all cohorts to assess whether depressive symptoms explained the association between CM and CVD. Finally, we further explored its indirect effects in multiple CVD comorbidities and gender groups.ResultsA total of 114,707 participants were included in the analysis, of which 50.14% reported CM. Our study demonstrated a strong association between CM scores and increased risk of CVD or depressive symptoms. Mediation analysis indicated that depressive symptoms accounted for 31.03% to 55.28% of the total effect for single CVD comorbidities, and 22.93% to 36.46% for multiple CVD comorbidities. Interestingly, across gender groups, males had a higher proportion of depressive symptoms mediating the association between the two.ConclusionThe research results remind us to pay attention to the impact of psychological factors on the CM population, so as to reduce the incidence rate of different types of CVDs.